The FORMULATION, CHARACTERIZATION, AND ANTIOXIDANT ACTIVITY OF TRANSPARENT SOAP CONTAINING MUNG BEAN SEEDS AND SPROUTS (Vigna radiata L.) - Lia Agustina; Tria Kartika Rahayu; David Raditya Soehartono; Ninis Yuliati; Chin Siang Kue (FACULTY OF PHARMACY, INSTITUT ILMU KESEHATAN BHAKTI WIYATA, 2026)
Background: Transparent solid soap is an innovative cosmetic product designed to improve aesthetic value and consumer acceptance. The incorporation of natural antioxidants has attracted growing interest due to their protective effects against free radicals. Mung bean (Vigna radiata L.), particularly its seeds and sprouts, exhibits antioxidant activity associated with flavonoid compounds, yet its application in transparent soap formulations remains limited. Objective: This study aimed to evaluate the physical quality and antioxidant activity of transparent soap formulations containing mung bean (Vigna radiata L.) seeds and sprouts. Method: Mung bean seeds and sprouts were dried, pulverized into powder, and subjected to phytochemical screening for flavonoid. Each powder was incorporated into transparent solid soap formulations. Antioxidant activity was evaluated in vitro using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. Commercial soap with known antioxidant activity was used as a positive control, while soap base without mung bean powder served as a negative control. Physical quality evaluation included organoleptic, pH, wetting test, skin irritation test, and stability assay. Conclusion: The incorporation of mung bean seed and sprout powders influenced the physical characteristics of transparent soap and provided antioxidant activity. Transparent soap containing mung bean sprouts exhibited stronger antioxidant activity, indicated by a lower IC₅₀ value, compared to soap containing mung bean seeds, suggesting that mung bean sprouts are a more effective natural antioxidant source.